The Impact of the Sorogan Method on Understanding the Sullamut Taufiq Book at the Nurul Iman Islamic Boarding School in Ciawigebang Village - Sopian Asep Nugraha; Sopandi Sopandi; Efit Fitria Agustianty (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The research conducted at the Nurul Iman Islamic Boarding School in Ciawigebang, Kuningan, aimed to obtain data on the use of the sorogan method, to determine the understanding of the Sullamut Taufiq book among male students, and to determine the effect of the sorogan method on their understanding of the Sullamut Taufiq book. The type of research conducted by the researcher was quantitative. In this study, the researcher used several techniques, as follows: 1) Data collection techniques through observation, interviews, and questionnaires. 2) Validity and reliability tests for the questionnaire. 3) Data analysis using percentage formulas (frequency distribution), classical assumption tests, regression test requirements (normality and linearity tests), product-moment correlation, regression tests, and determination tests. From the results of this study, it can be concluded that: The use of the sorogan method in teaching the Sullamut Taufiq book at the Nurul Iman Islamic Boarding School in Ciawigebang is categorized as Very Good with a score of 84.61%. The understanding of the Sullamut Taufiq book among male students at the Nurul Iman Islamic Boarding School in Ciawigebang is categorized as Very Good with a score of 83.35%. The influence of the use of the sorogan method on the understanding of the Sullamut Taufiq book among male students at the Nurul Iman Islamic Boarding School in Ciawigebang is 68.2%, while the remaining 31.8% is influenced by other factors.